2021
DOI: 10.3389/fimmu.2021.622001
|View full text |Cite
|
Sign up to set email alerts
|

Repurposing of the Antiepileptic Drug Levetiracetam to Restrain Neuroendocrine Prostate Cancer and Inhibit Mast Cell Support to Adenocarcinoma

Abstract: A relevant fraction of castration-resistant prostate cancers (CRPC) evolve into fatal neuroendocrine (NEPC) tumors in resistance to androgen deprivation and/or inhibitors of androgen receptor pathway. Therefore, effective drugs against both CRPC and NEPC are needed. We have previously described a dual role of mast cells (MCs) in prostate cancer, being capable to promote adenocarcinoma but also to restrain NEPC. This finding suggests that a molecule targeting both MCs and NEPC cells could be effective against p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…Thus, levetiracetam may inhibit the development of neuroendocrine PC after androgen deprivation therapy and block the progression of adenocarcinoma through the inhibition of mast cells. On the other hand, like valproic acid, it also inhibits HDAC, but this study demonstrated that extremely high doses of levetiracetam are required to cause these effects [ 57 ].…”
Section: Pharmacotherapeutic Groups With Potential Efficacy In Pc Tre...mentioning
confidence: 99%
“…Thus, levetiracetam may inhibit the development of neuroendocrine PC after androgen deprivation therapy and block the progression of adenocarcinoma through the inhibition of mast cells. On the other hand, like valproic acid, it also inhibits HDAC, but this study demonstrated that extremely high doses of levetiracetam are required to cause these effects [ 57 ].…”
Section: Pharmacotherapeutic Groups With Potential Efficacy In Pc Tre...mentioning
confidence: 99%
“…Recently, we discovered a new way to prevent MC degranulation by utilizing the antiepileptic drug levetiracetam [ 86 ], which is administered to avoid and mitigate seizures in patients [ 87 ]. Levetiracetam targets the synaptic vesicle protein 2A (SV2A) [ 88 ]—mainly present in neural and endocrine cells and involved in cell exocytosis [ 89 ]—and we found that this protein is also expressed by prostate cancer-infiltrating MCs [ 86 ]. We demonstrated that levetiracetam can inhibit MC degranulation and, in particular, the release of MMP9, thus restraining the pro-adenocarcinoma activity of MCs in TRAMP mice [ 86 ].…”
Section: Therapies Aimed At Targeting Mcs In Cancermentioning
confidence: 99%
“…Levetiracetam targets the synaptic vesicle protein 2A (SV2A) [ 88 ]—mainly present in neural and endocrine cells and involved in cell exocytosis [ 89 ]—and we found that this protein is also expressed by prostate cancer-infiltrating MCs [ 86 ]. We demonstrated that levetiracetam can inhibit MC degranulation and, in particular, the release of MMP9, thus restraining the pro-adenocarcinoma activity of MCs in TRAMP mice [ 86 ]. Furthermore, we also found the expression of SV2A in neuroendocrine prostate cancer and proved that, in this preclinical model, levetiracetam was also able to prevent neuroendocrine differentiation of adenocarcinoma after hormone therapy [ 86 ].…”
Section: Therapies Aimed At Targeting Mcs In Cancermentioning
confidence: 99%
“…Identification and repurposing of specific drugs such as AED may provide new therapeutic indications for substances with established safety profiles, potentially lower overall development costs, and shorter development timelines [ 3 , 4 ]. In addition to cancer cell cycle arrest, differentiation, and cell death, HDACi also moderates angiogenesis and modifies the immune response.…”
Section: Introductionmentioning
confidence: 99%